Optimally Oriented Remote Triggering in the Coso Geothermal Region. Issue 8 (9th August 2020) - Alfaro‐Diaz, Richard; Velasco, Aaron A.; Pankow, Kristine L.; Kilb, Debi
Abstract: Defining the nature of faulting, the stress needed to trigger earthquakes, and the stress state of faults remains fundamental to understanding the earthquake cycle. Studying remote dynamic triggering allows us to probe faults to systemically address the fundamental physical mechanisms of faulting. Using 13 years of data (2004–2016) from the EarthScope USArray Transportable Array and the Southern California Seismic Network, we search for remotely triggered seismicity in an extended region encompassing the Coso Geothermal Field (CGF+), California. We first apply a short term to long‐term average ratio detector to high‐pass (5 Hz) filtered waveforms spanning ±5 hr encompassing 211 M  ≥ 7 global earthquakes. We visually inspect these waveforms to identify uncatalogued local earthquakes. We use the augmented local earthquake catalog to investigate remote earthquake triggering in the CGF+ region. Of the 211 remote mainshocks, we find 32 (15%) produce a statistically significant increase in seismicity following the P wave arrival in CGF+. An additional nine mainshocks had local earthquakes coincident with the surface waves passage but lacked a significant rate increase. Of the 41 (19%) triggering mainshocks, 28 and 13 exhibit instantaneous and delayed triggering, respectively. We find no correlation between triggering and mainshock depth, peak dynamic stress, nor mainshock focal mechanism type. Instead, results suggest the CGF+ may be optimally oriented for remote triggering from mainshocks in the West Pacific and South America and propose the reason for this is that the transient dynamic stresses align favorably with the local stress field (most compressive horizontal stress, SHmax) to promote triggering. Plain Language Summary: Using 13 years of earthquake data (2004–2016) from the EarthScope USArray Transportable Array and the Southern California Seismic Network, we search for remotely triggered earthquakes in an extended region encompassing the Coso Geothermal Field (CGF+), California. Analyzing 211 M  ≥ 7 global earthquakes we identify 41 earthquakes consistent with remote triggering in the CGF+. Of these 41 triggering mainshocks, the back azimuths primarily range between ~70–100° (35, West Pacific) and ~240–300° (6, South America). Earthquakes from these two locations will produce seismic waves across our study region that geometrically align with the local stress field in a way that is most conducive to local earthquake triggering. We conclude that the fault geometry and local stress orientations in the CGF+ region are uniquely positioned to host remotely triggered earthquakes following large earthquakes originating from the West Pacific and South America. Key Points: Remote dynamic triggering preferentially occurs when wave propagation is perpendicular to the local stress (most compressive horizontal stress, SHmax) within the extended Coso Geothermal Field (CGF+) study region Observations suggest fault geometry and stress field orientation within the CGF+ region is uniquely positioned to be triggered by earthquakes originating from the West Pacific and South America Of the 211 large ( M  ≥ 7) earthquakes studied, 41 (~19%) are consistent with remote dynamic triggering in the CGF+ region